Demographic Limitations of Reclamation and Development of the Arctic Areas of the Far East of Russia - I. Sidorkina , Zinaida; L. Ushakova, Valentina (International Journal of Psychosocial Rehabilitation, 2020)
The present research analyzes demographic processes in a geopolitically and economically important region—the Chukotka Autonomous Okrug (ChAO), located on the northeastern borders of Russia and fully included in its Arctic zone. The long-term demographic processes (from 1939 to the present) are regarded, and the main factors that determine their focus and scope are identified. The authors note that demographic processes here occurred with different intensity and identify sometimes multidirectional stages in settlement and economic development, according to these criteria. A significant dependence of migration growth on the creation of large extractive industries in the region determined the level of economic well-being of the population and the region as a whole. The research substantiates that the resulting outflow of the population is also associated with the ‘curtailment’ of extractive industries in 1985-1989 in connection with the ‘perestroika’ reforms. The dynamics of natural population growth over the entire analyzed period is also largely ‘linked’ to periods of active development of mineral resources and ‘perestroika’ reforms. Such features (which closely correlate with highly efficient extractive industries) of the demographic potential formation in the considered region and in the Northeast of Russia as a whole should be taken into account when designing socio-economic development programs and concepts of demographic policy. The present study statistically analyzes and estimates the structure of migration flows, causes of death, life expectancy, etc., which also affect the demographic situation in the region. Measures are suggested to maintain demographic growth in the face of declining birthrate reserves, aging populations, maintaining migration outflows, losses of the able-bodied population to external causes of death, etc.